Analisis Hidrodinamik Rotary Distributor Hidraulik Teknologi Ega-Sattira dan Pengembangannya untuk Irigasi Tetes-Putar - Eko Winar Irianto (Balai Teknik Irigasi, 2016)
Trickling filter is a wastewater treatment technology which has high effiency on organics reduction but low energy on its operation. Ega Sattira is the combined technology between constructed wetland and trickling filter technologies. One of the success on its treatment process is due to the hydraulic-rotary distributor. Hydrodynamic analysis on hydraulic-rotary distributor is required for making better and more efficient on Ega-Sattira’s operation and process system. The research objectives are: (a) to analize and formulate the hydrodynamic model on movement-force mechanisme of hydraulic-rotary distributor on Ega Sattira technology; (b) to utilize the the phenomenon of hydraulic-rotary distributor as an alternatif of drip-rotary irrigation technique which is part of water efficient irrigation; 3) to propose the basic desain on drip-rotary irrigation system that is easy, cost efficient and efficient in operation and maintenance. The results of hydrodynamic analysis shows that rotation number per time unit is directly proportional to the gravity acceleration, friction coefficient and root of the water level in the tank and critical flow coefficient, but inversely proportional to the diameter of rotary-distributor pipe. Calibration trial result between counting rotation and actual rotation resulted the equation Y= 0,0014X dengan r2= 0,82. The formulation result can be applied to the planning of hydraulic-rotary irrigation system supporting the technology of water-saving irrigation.